AN ERROR ANALYSIS IN MOOD MADE BY THE SEVENTH SEMESTER ENGLISH STUDENTS OF STKIP BUDIDAYA BINJAI IN THE YEAR 2017/2018 - Yusrah (LPPM STKIP AL MAKSUM, 2020)
This research was purposed to find out the types of error and the sources of error made by the seventh semester English students of STKIP Budidaya Binjai in theyear 2017/2018. The researcher formulated the problems of this research were: “What types of error are made by students in Mood?” and “What sources of errors are made by students in Mood?”. The design of the research was a qualitative research. Based on the results of the data analysis, the findings of this research can be stated as follows: (1) The seventh semester English students of STKIP Budidaya Binjai made error in writing Mood of the sentences. (2) The types of error which students made were: Omission, Addition (double marking), Misformation and Misordering. The type of error which the most dominantly made by the students was error of Omission. (3) The sources of error which students made were: Interlingual Transfer, Intralingual Transfer, Context of Learning andCommunication Strategy. The source of error which the most dominantly made by the students was Communication strategy.